2021
DOI: 10.1016/j.xfre.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight and body mass index on serum progesterone values and live birth rate in cryopreserved in vitro fertilization cycles

Abstract: Objective: To determine if weight or body mass index (BMI) affects the serum progesterone level at the time of the pregnancy test in cryopreserved blastocyst transfer cycles and to determine if those serum progesterone levels affect live births. Design: Retrospective cohort study. Setting: US academic medical center. Patient(s): Six hundred thirty-three patients undergoing their first cryopreserved embryo transfer cycle. Intervention(s): None. Main Outcome Measure(s): The primary outcome was the serum progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Several studies showed that as BMI in women increases, the level of serum progesterone decreases. [48][49][50][51] Lowering progesterone through use of oral contraceptives drastically reduced Tregs in women, 52 consistent with the suggestion that BMI-associated decreases in progesterone lower Tregs in obesity and thus potentiate shifts in inflammatory profiles. Data that complement effects on Tregs showed that progesterone (at specific concentrations) activates CD4 + cells and downregulates numerous T cell cytokines including those associated with Th1, Th2, and Th17 subsets.…”
Section: Ob E S It Y In Female Mice and Humanssupporting
confidence: 69%
“…Several studies showed that as BMI in women increases, the level of serum progesterone decreases. [48][49][50][51] Lowering progesterone through use of oral contraceptives drastically reduced Tregs in women, 52 consistent with the suggestion that BMI-associated decreases in progesterone lower Tregs in obesity and thus potentiate shifts in inflammatory profiles. Data that complement effects on Tregs showed that progesterone (at specific concentrations) activates CD4 + cells and downregulates numerous T cell cytokines including those associated with Th1, Th2, and Th17 subsets.…”
Section: Ob E S It Y In Female Mice and Humanssupporting
confidence: 69%
“…Most importantly, baseline E2, FSH level, and E2 and P level on triggering day were significantly lower in the overweight/obese group compared to the normal weight group, consistent with findings from several prior studies ( 12 , 31 34 ). For instance, previous research has reported that in cryopreserved blastocyst transfer cycles, serum P levels on the day of pregnancy testing were <15 ng/mL in 29% of women weighing >90.7 kg, versus 3% in those weighing <68 kg ( 32 ). In addition, in intrauterine insemination cycles for patients <35 years old, serum E2, LH, and P levels were negatively correlated with BMI on hCG day ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systemically, progesterone exerts a regulatory role upon the innate and acquired immune responses, resulting in an inhibition of cytotoxicity and the induction of immune tolerance required for successful implantation ( Szekeres-Bartho, 2018 ; Shah et al , 2019 ). The bioavailability of progesterone administered vaginally varies according to many factors including dose, frequency of administration, the woman’s age and BMI, the saturability of vaginal and uterine progesterone receptors, and the ability of the epithelial lining to absorb the drug into the systemic circulation ( MacLaughlin and Richardson, 1976 ; Levy et al , 1980 ; Archer et al , 1995 ; González-Foruria et al , 2020 ; Whynott et al , 2021 ). There is, hence, biological plausibility to the hypothesis that in women with a low level of circulating progesterone, the addition of a systemic route of exogenous progesterone administration may compensate, at least partly, for low absorption rates where there is impaired local absorption.…”
Section: Discussionmentioning
confidence: 99%